Satellite DVB-RCS VSAT standards for fixed and mobile applications - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2018)
The growing demand for communications bandwidth over all wireless media has motivated the introduction of compact satellite com-munications solutions that provide bi-directional services at greater than 90 Mb/s known as Digital Video Broadcasting-Return Channel via Satellite (DVB-RCS). Current applications may demand rapid installation at fixed locations as well as mobile platforms, such as stationary and moving vehicles, manned and unmanned aircraft, and ships on the oceans. More than a basic introduction, this course presents the specific approaches for designing a broadband satellite network using L/C, Ku, and Ka-bands, and should allow participants to configure major space and ground architecture, evaluate sources of antennas technology, RF electronics, and select the most appropri-ate satellite architecture, spot or regional coverage, bandwidth and services. Applications to commercial and government users are de-scribed as well as compliance with international radio regulations. This paper will provide a case study of the implementation of DVB-RCS scenario for Military Applications for Navy, Land and Aeronautical military platforms. The design and implementation DVB-RCS satellite constellation, development ground infrastructure of the Hub or Gateway as Ground Earth Station (GES) with antenna system and users network, the return link demodulation method, resource management scheme, fixed and mobile terminal structure including antenna configurations are described. The paper also addresses DVB-RCS applications that provide both IPTV and IPPC high-speed Internet base on DVB-S/DVB-RCS standards to the commercial and military passengers and crews for land, maritime and air vehicles, including E-education, E-medicine, E-banking (ATM), Defense Information Management (DIM), Voice over IP and Voice, Data and Video over IP (VDVoIP) and so on.Â